Supplementing Freezing Medium with Crocin Exerts a Protective Effect on Bovine Spermatozoa Through the Modulation of a Heat Shock-Mediated Apoptotic Pathway - Vasiliki Sapanidou; Maria P. Tsantarliotou; Konstantinos Feidantsis; Eleni E. Tzekaki; Georgios Kourousekos; Sophia N. Lavrentiadou (Molecules)
The supplementation of freezing medium with crocin results in an amelioration of post-thawing sperm quality, as determined by motility and viability. This study aimed to examine the molecular mechanisms underlying the ameliorative effect of crocin. Bovine spermatozoa were cryopreserved in a freezing medium supplemented with 0, 0.5, or 1 mM of crocin. Sperm lysates were evaluated for their redox status and the expression of proteins implicated in the heat stress response (HSR) and apoptosis. Crocin protected spermatozoa from the accumulation of superoxide anion and ameliorated their post-thawing antioxidant capacity in terms of ROS scavenging activity and glutathione content. Moreover, crocin decreased the levels of inducible nitric oxide synthase (iNOS), while it increased superoxide dimsutase-1 (SOD-1) levels. These effects were associated with an inhibition of apoptosis, as evidenced by a decreased Bax/Bcl-2 protein ratio and decreased levels of caspase-cleaved substrates. Finally, crocin affected the heat shock response of spermatozoa, since it upregulated the levels of heat shock proteins (Hsp) 60, 70, and 90. In conclusion, the addition of crocin to the freezing medium ensured controlled amounts of ROS, enhanced the antioxidant capacity of spermatozoa, and upregulated the anti-apoptotic proteins and Hsps, thus contributing to the maintenance of cellular homeostasis.